Socio-economic study of mud crab (Scylla serrata) households in Bengkulu Province, Indonesia - Cahyadinata, I.; Nusril.; Nopiana, M. (International Journal of Agricultural Technology, 2025)
Results indicated that the food security of mud crab fishermen households in Bengkulu Province, Indonesia was generally secured. It was found that 92% of fishermen’s households were very secure, 4% were quite secured, and 4% were less secure. Meanwhile, based on multidimensional poverty category of mud crab fishermen households was not impoverished. Overall, 67% of people were not poor, 22% were vulnerable poor, 3% were poor, and 7% were very poor. Furthermore, the welfare of mud crab fishermen households is found to be in the category of high welfare. Those included in high welfare was 53% and in moderate category is 47%. In addition, the feasibility of mud crab fishery business carried out by fishermen which was in the feasible category with a BC ratio of 3.04. The socio-economic status of fishermen households as indicated by the sufficient category were grouped into good, sufficient and bad were accounted for 27.9%, 70.8%, and 1.3%, respectively. Improving the socio-economic status of fishermen’s households could be done through the expansion of the mud crab fishing industry. Then, increasing income would increase food security, reduce multidimensional poverty, enhance welfare and raise business feasibility. Increasing income could be completed by enlarging the volume mud crabs caught by fishermen as well as selectively selling bigger size to have higher revenue.